Eating disorders : a comprehensive guide to medical care and complications - Mehler, Philip S.; Andersen, Arnold E. (Johns Hopkins University Press, 2022)
"A guide for health care providers on how to diagnosis, treat, and care for those with eating disorders. Four new chapters have been added to the fourth edition"--